Relationship of MMP-9 with the clinical course of apical periodontitis and the main bacterial species in the oral microbiota - Özdemir, Burcu; Erşahan, Şeyda; Özçelik, Fatih; Erdem Hepşenoğlu, Yelda; Şirin, Dursun Ali; Topbaş, Celalettin (My University, 2024)
Bacterial products, host immune cells and cytokines have been reported to play an important role in the pathogenesis of apical periodontitis (AP). This study aimed to determine the main bacterial species in the microbiota as gram positive and negative and to compare the relationship between matrix metalloproteinase (MMP)-9 and tumor necrosis factor (TNF)-? with controlled patient groups. 60 patients with AP and extraction indication were included in the study. 30 systemically healthy volunteers without AP were selected as the control group. After access cavity preparation, an initial microbiologic sample (S1) was taken from the root canal. After atraumatic extraction of the tooth, a second microbial sample (S2) was taken from the extraradicular region. After bacterial DNA extraction, 16S rRNA gene primer was designed for sequence analysis. Bacterial community profiling was made by Sanger sequencing of the PCR products. In addition, serum MMP-9 and TNF-? levels were measured from all patients. TNF-? levels of the AP group were higher than the control group, while MMP-9 levels were found to be lower (p = 0.0264 and p = 0.0146, respectively). There was no difference in the main bacterial species isolated from the samples taken from the intracanal and extraradicular region of the tooth with AP (p = 0.714). The main bacterial species in the intracanal region of the tooth with AP are similar to the main bacterial species in the extraradicular region. The pathophysiology of the tooth with AP is associated with low MMP-9 and high TNF-?, independent of the bacterial species in the intracanal and extraradicular regions.
Keywords: Apical Periodontitis; Bacteria Species; Matrix Metalloproteinase; Root Canal; Tumor Necrosis Factor